Peningkatan Pemahaman Konsep Siswa Pada Materi Lingkaran Dengan Menggunakan Media Manipulatif - Tatik Retno Murniasih (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2018)
Based on this initial observation on the students of grade VIII, it was found that the ability of the student’s concept understanding on the subject about circle was low.  Only 40% of the students were included in the category of understanding the concept. Manipulative media was needed to increase student’s concept understanding on the subject about circle. This research aimed to describe the learning steps using manipulative media to increase student’s concept understanding on the subject about circle. Class Action Research using Kemmis and McTaggart model was applied on this research. The steps of Kemmis and McTaggart model consist of: planning, action, observation, and reflection. The instruments used in this research were: examination sheet, learning observation sheet, and interview guidance. This research used manipulative media on the subject about circle, which could increase student’s concept understanding. The research result showed that: a) there was 30% increase in student’s concept understanding, which was 50% of students in cycle I were in the cathegory of understanding the concept, it was increased into 80% on cycle II, and b) there was 5% increase of learning mastery, which was 85% of students learning mastery in cycle I were increased into 90% on cycle II.